REOVASOGRAPHY INDICES AMONG PERSONS WITH DIFFERENT LEVEL OF PHYSICAL ACTIVITY - Pilipchuck, V.V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The experimental work showsthe results of the limb reovasography investigation in sportsmen and non-sportsmen.It has been shown that regular physical activity can increase elasticy and blood-fill of vessels.